Guerre, guerre civile, guerre révolutionnaire : la violence en héritage dans l'Italie républicaine, 1945-1980 - Virgile Cirefice; Grégoire Le Quang (Amnis)
For Italy, the end of the Second World War is a key step that puts an end to two decades of fascism. It is an episode of fratricidal violence which can be described as a war of liberation, a civil war and, partly, a class war - all at the same time. While the historiography of fascist totalitarianism and civil war has been profoundly renewed recently, the long-term significance of the legacy of these events is only partially explored. First, there is the question of the conditions for a return to peace. This refers to the modalities of the pursuit of fascist leaders and Nazi collaborators, as well as to the sometimes radical challenge of the democratic order set up at the Liberation. The process of democratic transition is indeed threatened by the permanence of forms of political violence and by rhetorics of criminalization of the enemy, which are exacerbated by the entry into the Cold War. Political cultures continue to be inspired by the patterns inherited from the war period. During the 1960s and 1970s, anti-communist rhetorics and the resurgence of antifascism also contributed to dramatizing political oppositions, until the season of terror that culminated in the late 1970s. As a result, there is a persistent confusion between war and peace in Italy that allows us to question the shadow of the war experience over more than three decades.